X-ray Structure Determination, Antioxidant Voltammetry Studies of Butein and 2′,4′-Dihydroxy-3,4-dimethoxychalcone. Computational Studies of 4 Structurally Related 2′,4′-diOH Chalcones to Examine Their Antimalarial Activity by Binding to Falcipain-2 - Ijeoma Okoye (MDPI AG, 2021)
Malaria is a huge global health burden with resistance to currently available medicines resulting in the search for newer antimalarial compounds from traditional medicinal plants in malaria-endemic regions. Previous studies on two chalcones, homobutein and 5-prenylbutein, present in E. abyssinica, have shown moderate antiplasmodial activity. Here, we describe results from experimental and computational investigations of four structurally related chalcones, butein, 2′,4′-dihydroxy-3,4-dimethoxychalcone (DHDM), homobutein and 5-prenylbutein to elucidate possible molecular mechanisms by which these compounds clear malaria parasites. The crystal structures of butein and DHDM show that butein engages in more hydrogen bonding and consequently, more intermolecular interactions than DHDM. Rotating ring-disk electrode (RRDE) voltammetry results show that butein has a higher antioxidant activity towards the superoxide radical anion compared to DHDM. Computational docking experiments were conducted to examine the inhibitory potential of all four compounds on falcipain-2, a cysteine protease that is involved in the degradation of hemoglobin in plasmodium-infected red blood cells of the host. Overall, this work suggests butein as a better antimalarial compound due to its structural features which allow it to have greater intermolecular interactions, higher antioxidant activity and to create a covalent complex at the active site of falcipain-2.